Not just fish, but the future - Kang, Donggu; Choi, Ji-Hee; Park, Yun-Gwi; Choi, Hyung Kyu; Moon, Sung-Hwan; Yang, Gi Hoon (Frontiers in Sustainable Food Systems, 2025)
Fish are an important source of animal protein, providing 17% of the world's meat consumption. More than 3 billion people rely on fish for 20 % of their daily protein intake. In addition to a high protein content, fish contain essential fatty acids which are beneficial to human health. However, this key food source will be depleted by 2048 if current global trends of climate change, overfishing, and pollution continue. Considering the threat to sustainability and the need for marine ecosystem recovery, “clean fish”—grown in a laboratory—could be a potential solution. Since cell-based fish are produced in clean rooms where airborne particulates, contaminants, and pollutants are kept within strict limits, these engineered fish do not contain any health-risking factors. Therefore, clean fish can provide people with sustainable and nutritional diets while contributing to the recovery of the marine ecosystem. This review will discuss topics, including cell-based fish, the edible part of fish, technology, and commercialization.